Захист конфіденційної інформації в мережі internet та соціальних мережах - Бурцева, К. О. (ХНУРЕ, 2024)
The paper highlights the importance of cybersecurity in today's world, where the Internet is the primary platform for communication, work, and entertainment. It details various threats, such as hacking attacks, phishing, and mal ware, which can lead to the loss of sensitive data and financial losses. Addition ally, the paper discusses security measures, including data encryption, secure network access protocols, and two-factor authentication, as key elements in protecting information on the Internet and social networks.
Keywords: захист конфіденційної інформації; конфіденційна інформація